Gamification in Islamic Education: Increasing Student Motivation Through Digital Platformsontent - Laila Ngindana Zulfa (Islamic Studies in the World, 2025)
Background. Traditional pedagogical approaches in Islamic education often face challenges in maintaining high levels of student motivation and engagement, particularly within digital learning environments. The integration of gamification, the application of game-design elements in non-game contexts, presents a promising strategy to address this issue by transforming the learning experience into a more interactive and rewarding process. Purpose. This research aims to investigate and measure the impact of a gamified digital learning platform on the intrinsic and extrinsic motivation of junior high school students in the context of Islamic education subjects, such as Qur’anic studies and Islamic history. Method. A quasi-experimental research design involving a pre-test and post-test control group was employed. The sample consisted of 120 junior high school students, who were divided into an experimental group that used a gamified digital platform and a control group that used a conventional digital platform. Results. The findings revealed a statistically significant increase in overall motivation scores for the experimental group compared to the control group. Specifically, the gamified elements of points, badges, and leaderboards were strongly correlated with higher levels of perceived competence and effort. The experimental group also improvement in learning outcomes, indicating a positive relationship between enhanced motivation and academic performance. Conclusion. Gamification serves as an effective pedagogical strategy to significantly enhance student motivation and engagement in Islamic education. The strategic implementation of game mechanics on digital platforms can create a more dynamic and compelling learning environment, leading to improved academic achievement.